2020
DOI: 10.1002/hed.26578
|View full text |Cite
|
Sign up to set email alerts
|

Increased rate of recurrence and high rate of salvage in patients with human papillomavirus–associated oropharyngeal squamous cell carcinoma with adverse features treated with primary surgery without recommended adjuvant therapy

Abstract: Background: Some patients with human papillomavirus (HPV)-associated oropharyngeal squamous cell carcinoma (OPSCC) do not receive guidelinerecommended postoperative radiation therapy (PORT) following primary transoral robotic surgery (TORS). Methods: Three-hundred and sixty-four patients with treatment-naïve, HPVassociated OPSCC were recommended to receive PORT based on clinicopathological features following TORS. Patients were stratified based on if they received PORT. Oncologic outcomes were compared. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
(44 reference statements)
0
26
0
Order By: Relevance
“…HPV status was determined based on p16 immunohistochemistry as previously described. 8,9 A negative margin was defined as a minimum of 2 mm and a close margin was defined as less than 2 mm. All surgeries were performed with curative intent.…”
Section: Cohort Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV status was determined based on p16 immunohistochemistry as previously described. 8,9 A negative margin was defined as a minimum of 2 mm and a close margin was defined as less than 2 mm. All surgeries were performed with curative intent.…”
Section: Cohort Selectionmentioning
confidence: 99%
“…7 We have previously shown that patients with HPV+ OPSCC treated with primary transoral robotic surgery (TORS) who do not receive National Comprehensive Cancer Network (NCCN)-guideline recommended postoperative radiation (PORT) have an increased risk of LRR but high salvage rates and similar survival to patients who receive optimal adjuvant therapy. 8 In the current study, we aimed to describe the outcomes of patients suffering LRR who did receive guideline-compliant adjuvant therapy and evaluate for factors associated with LRR in this population. In addition, we aimed to identify features associated with failure of salvage therapy which might impact patient counseling, clinical management of LRR, and clinical trial design.…”
Section: Introductionmentioning
confidence: 99%
“…Although this period is relatively limited in duration, multiple studies have demonstrated short median times to local recurrence in surgically treated HPV+OPSCC ranging from 0.7 to 1.6 years. [1][2][3] In our study, no patient experienced local recurrence beyond 18 months of follow-up. While we noted in our study discussion that these patients remain at risk for recurrence, this study duration appears adequate to draw conclusions regarding local control in this patient population.…”
mentioning
confidence: 48%
“…Other studies have noted rates of lymphovascular invasion in single-modality surgical patients ranging from 13.4% to 18.2% and rates of perineural invasion ranging from 3.5% to 19.6%. 2,3 We agree that quality of life (QOL) remains a critical area of ongoing research in comparative study of treatment modalities but is beyond the scope of our study. The central impetus of avoiding adjuvant treatment in our patient population is precisely to improve long-term quality of life by minimizing adjuvant treatment sequelae while maintaining superior oncologic outcomes.…”
mentioning
confidence: 78%
See 1 more Smart Citation